The mufti and the state administration of Islam: some selected fatwas in contemporary Perlis, Malaysia (Mufti dan pentadbiran Islam negeri: beberapa fatwa terpilih di Perlis, Malaysia) - Ismail, Norbani (International Islamic University Malaysia, 2019)
The paper explores an Islamic institution in contemporary Malaysia. It studies the roles of the Mufti and the State mufti office as actors in issuing and informing religious edicts (fatwas) in Perlis, a northern state of Peninsular Malaysia. As an autonomous state institution coupled with the official state’s subscription to Ahlul Sunna wal Jama’ah as a principle in interpreting Islam, the state has issued fatwas that are perceived to embrace the religious nuances of contemporary realities. The paper examines the fatwas issued by Perlis’s Mufti Office on establishing paternity claim, unilateral conversion and child custody, child vaccination, and woman leaving marital home. The fatwas unveil a meticulous process that involves consulting relevant experts in both the religious scholarly fields and the modern scientific disciplines. The fatwas indicate deep appreciation and use of centuries old Islamic religious body. The fatwas also reflect the state’s religious institution’s commitment to and understanding of protecting the basic rights of individuals as much as serving the public good.